Silver or cerium-promoted free radical cascade difunctionalization of o-vinylanilides with sodium aryl- or alkylsulfinates. Issue 4 (10th January 2019) - Wu, Jilai; Zong, Yuanyuan; Zhao, Chunxia; Yan, Qinqin; Sun, Lixian; Li, Yiming; Zhao, Jincan; Ge, Yaxin; Li, Zejiang
Abstract : An efficient cascade oxysulfonylation of o -vinylanilides with sodium aryl- or alkylsulfinates was developed for the synthesis of sulfonated benzoxazines. Abstract : An efficient cascade oxysulfonylation of o -vinylanilides with sodium aryl- or alkylsulfinates by a free radical mechanism has been developed, which provides a mild, facile and convenient method for the synthesis of various benzoxazines. Control experiments, including gram-level reactions and mechanistic studies, are involved in the reaction system.